2017
DOI: 10.1371/journal.pone.0175987
|View full text |Cite
|
Sign up to set email alerts
|

The long term outcome of micturition, defecation and sexual function after spinal surgery for cauda equina syndrome

Abstract: BackgroundCauda equina syndrome (CES) is a rare neurologic complication of lumbar herniated disc for which emergency surgical decompression should be undertaken. Despite the common belief that the restoration of functions that are affected by CES can take several years postoperatively, follow up seldom exceeds the first year after surgery. Long term outcome of especially micturition, defecation and sexual function—which are by definition affected in CES—are unknown. The aim of this study is to evaluate 1) post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
1
26
2
2
Order By: Relevance
“…Only two studies have tried to find a correlation between different clinical variables and SD by systematic statistical analy-sis. Few CES outcome studies have shown rates of SD greater than 50% at a mean of 2 months, 5 years, and 14 years of follow-up [16][17][18]. A meta-analysis revealed an overall rate of 43% in 322 patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have tried to find a correlation between different clinical variables and SD by systematic statistical analy-sis. Few CES outcome studies have shown rates of SD greater than 50% at a mean of 2 months, 5 years, and 14 years of follow-up [16][17][18]. A meta-analysis revealed an overall rate of 43% in 322 patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of long term outcomes after surgery for 46 CES patients had a mean follow up of 43 months [27]. Validated questionnaires and unvalidated semi structured interviews were used to assess long term outcomes of bladder, bowel, sexual and physical function.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a reflection that it is a rare syndrome so any attention or further research for the condition is actively engaged and welcomed by them suggesting the burden of data collection is not an issue with this patient group. A study reviewing the long-term outcomes after spinal surgery for CES showed that there was a real need for HCPs to spend sufficient time discussing the difficult issues and delivering prognostic information to patients regarding their outcomes [27]. This highlights the importance of recording and reporting the CESCOS outcomes for future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Die Rezidivrate im weiteren postoperativen Verlauf wird in der Literatur mit 18 -27 % angegeben [25,26].In einer Analyse der Patienten der Kontrollgruppe aus einer großen, randomisierten, kontrollierten Studie zum Annulusverschluss wurden Faktoren gesucht, die mit einem erhöhten Risiko für ein Rezidiv eines operativ behandelten Bandscheibenvorfalls einhergehen. Dabei zeigten die Ergebnisse, dass 64 von 253 Patienten, also 25,3 %, in dieser Gruppe ein Rezidiv erlitten.…”
Section: Rezidive Nach Lumbaler Bandscheibenoperationunclassified
“…Das Kaudasyndrom hatte vor der Operation im Durchschnitt 84 Stunden bestanden [25]. In einer weiteren Studie aus dieser Arbeitsgruppe konnte darüber hinaus nachgewiesen werden, dass auch im Langzeitverlauf (im Median 13,8 Jahre nach Operation) die Symptome persistieren und eine deutliche Beeinträchtigung der Lebensqualität für die Betroffenen darstellen [26]. In einem aktuellen Review schlussfolgert der Autor, dass es eine sehr große Heterogenität in der Beschreibung des klinisch-neurologischen Ergebnisses in den Studien gibt, was die Vergleichbarkeit erheblich erschwert.…”
Section: Spezialfall: Bandscheibenvorfall Mit Kaudasyndromunclassified